The perfect afternoon tea book : over 70 tea-time treats: a feast of cakes, biscuits and pastries, illustrated with 270 photographs - Wild, Antony , 1955-; Hill, Simona (Lorenz Books, 2009)
Afternoon tea is the quintessential English tradition that everyone loves to share. This delightful book provides all the classic recipes that you will need together with a history of the custom of afternoon tea